Euler Integral + Euler Series

Calculus Level 4

0 cos x e 2 π x 1 d x \int_0^{\infty} \dfrac{\cos \sqrt{x}}{e^{2\pi\sqrt{x}} - 1}\,dx

Find the closed form of the integral above. Submit your answer to 4 significant figures.

Note: e e is the Euler's number e 2.71828 e \approx 2.71828 .


The answer is 0.0793264057922.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
May 25, 2021

Note that the integral is I = 0 cos x e 2 π x 1 d x = n = 1 0 cos x e 2 π n x d x = 2 n = 1 0 u cos u e 2 π n u d u I \; = \; \int_0^\infty \frac{\cos \sqrt{x}}{e^{2\pi \sqrt{x}} - 1}\,dx \; = \; \sum_{n=1}^\infty \int_0^\infty \cos\sqrt{x} e^{-2\pi n \sqrt{x}}\,dx \; = \; 2\sum_{n=1}^\infty \int_0^\infty u\cos u e^{-2\pi n u}\,du Note that

0 u cos u e p u d u = d d p 0 cos u e p u d u = d d p p p 2 + 1 = p 2 1 ( p 2 + 1 ) 2 \int_0^\infty u \cos u e^{-pu}\,du \; = \; -\frac{d}{dp}\int_0^\infty \cos u e^{-pu}\,du \; =\; -\frac{d}{dp}\frac{p}{p^2+1} \; =\; \frac{p^2 - 1}{(p^2+ 1)^2}

for p > 0 p > 0 , and hence I = 2 n = 1 4 π 2 n 2 1 ( 4 π 2 n 2 + 1 ) 2 = 1 1 4 c o s e c h 2 1 2 I \; =\; 2\sum_{n=1}^\infty \frac{4\pi^2 n^2 - 1}{(4 \pi^2 n^2 + 1)^2} \; =\; 1 - \tfrac14\mathrm{cosech}^2\tfrac12 using some standard series identities, which means that I = 0.079326405792207681055 I = \boxed{0.079326405792207681055} .

nice solution @Mr Hennings

Aman Rajput - 2 weeks, 2 days ago

For the interested reader in accordance with @Mark Hennings beautiful solution the series identities used are,

Identity 1 : n = 1 1 4 π 2 n 2 + 1 = 1 4 coth ( 1 2 ) 1 2 \displaystyle \sum_{n=1}^\infty \dfrac{1}{4\pi^2 n^2+1} = \dfrac{1}{4}\coth\left(\dfrac{1}{2}\right)-\dfrac{1}{2}

Identity 2 : n = 1 ( 1 4 π 2 n 2 + 1 ) 2 = 1 8 coth ( 1 2 ) + 1 16 csch ( 1 2 ) 1 2 \displaystyle \sum_{n=1}^\infty \left(\dfrac{1}{4\pi^2 n^2+1}\right)^2 = \dfrac{1}{8}\coth\left(\dfrac{1}{2}\right)+\dfrac{1}{16}\text{csch}\left(\dfrac{1}{2}\right)-\dfrac{1}{2}

Dwaipayan Shikari
May 27, 2021

0 cos ( x ) e 2 π x 1 d x = substituting x = u 2 0 2 u cos ( u ) n = 1 e 2 π n u d u \displaystyle\int_0^∞ \dfrac{\cos(\sqrt{x})}{e^{2π\sqrt{x}}-1} dx =^{\textrm {substituting} {x=u^2} }\int_0^∞ 2u\cos(u)\sum_{n=1}^∞ e^{-2πnu} du

Considering cos ( u ) = e i u + e i u 2 \cos(u)= \dfrac{e^{iu} +e^{-iu}}{2} , the integral becomes

n = 1 0 u e u ( 2 π n i ) + u e u ( 2 π n + i ) d u \displaystyle \sum_{n=1}^∞ \int_0^∞ u e^{-u(2πn-i)} + ue^{-u(2πn+i)} du

= n = 1 1 ( 2 π n i ) 2 + 1 ( 2 π n + i ) 2 = 1 4 n = 1 1 ( π n i / 2 ) 2 + 1 ( π n + i / 2 ) 2 \displaystyle= \sum_{n=1}^∞ \dfrac{1}{(2πn-i)^2} +\dfrac{1}{(2πn+i)^2}=\dfrac{1}{4} \sum_{n=1}^∞ \dfrac{1}{(πn-i/2)^2} +\dfrac{1}{(πn+i/2)^2} Now n = 1 ( π n + x ) 2 = csc 2 ( x ) \sum_{n=-∞ }^∞ \dfrac{1}{(πn+x)^2} = \csc^2(x)

Here it is 1 4 n = 1 ( π n + i 2 ) 2 + 1 = 1 e ( e 1 ) 2 \displaystyle \dfrac{1}{4} \sum_{n=-∞}^∞ \dfrac{1}{(πn+\frac{i}{2})^2} +1 = 1-\dfrac{e}{(e-1)^2} See this question

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...